Analysis of particles size distribution on the agglomeration and shrinkage of alumina-zirconia compacts - A. A., Afuza; A. B., Hadzley; T., Norfauzi; A. A., Umar; M., Faiz; F., Naim; Kunlapat, Thongkaew (Universiti Malaysia Perlis (UniMAP), 2020)
The combination of Alumina and Zirconia has emerged as a promising ceramic structure for advance machine tool application. However, the particles of Alumina and Zirconia tend to agglomerate during mixture which affected shrinkage and dimension accuracy of the end product. This study focused on the analysis of the particle size of Alumina-Zirconia compacts and their relationship with the shrinkage and agglomerates. The particles size of single Alumina, Zirconia and ball-milled Alumina-Zirconia with 90-10 wt% ratio were examined by mastersizer. These powders then were compacted and sintered at 1400°C to examine their shrinkage. The results show that Alumina possesses larger particles size of 109.65 μm, which is 10 folds larger than Zirconia at 6.10 μm. When blended by ball mill, the AluminaZirconia particles were changed into 9.77 μm, showing that the ball mill to refine powder particles while reducing the risk of agglomeration. After sintering, the Alumina-Zirconia compacts were shrunk to maximum 9.56% when 75-25 wt% of Alumina-Zirconia. The combination of porosity, agglomerate and infiltration of zirconia between alumina grains were responsible for the shrinkage of Alumina-Zirconia compacts.